Prácticas de enseñanza de la lógica matemática en el nivel inicial II en la Unidad Educativa Nueva Primavera - Reinoso Cruz, Yadira Alexandra (2016)
This study has been realize with the aim to analyses pedagogical practices in initial education in the “ Nueva Primavera” Educative unit, in the logical mathematical signature that work constitute analysis and description, this work will detect problems which have been recurrent in the last years either by changing the policies, redistribution of time, working methods, curricular adaptations, as well the development of the class, management planning, uses of resources, strategies, activities and evaluation forms. The research problem develops because there is no research on the subject and the importance ascribed to mathematical logic. Mapping initial pedagogical practices to the logical mathematics in initial education would be the main objective of this work and they will base the construction of the same, it will be the description of the different tasks, actions, ideas, interrelation ships which are involved in the educational process. Observations will be realized to build this work and they will be registered in records after being completed then they would be taken to an area where they are going to be described, taking into account the different concepts and theoretical approaches as constructivist theory, evolutionary development and meaningful learning. The qualitative focus and the ethnographic method will contribute to the development of this work, as well the application of instruments and techniques designed to compile and to analyze information. This investigation will permit identify how teachers are developing they daily labor and what pedagogical method are they using to get and obtain a meaningful and long-life learning